PENGARUH MOTIVASI, PELATIHAN, DAN DISIPLIN KERJA TERHADAPi KINERJA GURU SD NEGERI DI DESA UJUNG BATU TIMUR - Malau Arinah Asri; Garnasih Lestari Raden; Marhadi Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The purpose of this study was to determine the effect of motivation,training, and work discipline on the performance of elementary school teachers inthe village of Ujung Batu Timur. The population in this study were all elementaryschool teachers in the village of Ujung Batu Timur. The sampling technique usedthe census method, and the sample in this study amounted to 33 teachers. Thevariables studied were motivation, training, and work discipline as independentvariables, and teacher performance as the dependent variable. The datacollection method used is a questionnaire/questionnaire. The data analysismethod is in the form of PLS (Partial Least Squares) and the application used isSmartPlS version 3.0. The model tested in this study is the outer model(corvergent validity, discriminant validity, composite reliability), and the innermodel (R-square). The results of this study indicate that 1) There is an influencebetween motivation on the performance of State Elementary School teachers inUjung Batu Timur Village. 2) There is an influence between training on theperformance of State Elementary School teachers in Ujung Batu Timur Village. 3)There is an influence between work discipline on the performance of SD Negeriteachers in Ujung Batu Timur Village. 4) There is an influence betweenmotivation, training, and work discipline simultaneously on the performance ofState Elementary School teachers in Ujung Batu Timur Village. Keywords : Motivation, Training, Work Discipline, Teacher Performance